2017
DOI: 10.1002/mrm.26837
|View full text |Cite
|
Sign up to set email alerts
|

Application of pattern recognition techniques for classification of pediatric brain tumors by in vivo 3T 1H‐MR spectroscopy—A multi‐center study

Abstract: Purpose3T magnetic resonance scanners have boosted clinical application of 1H‐MR spectroscopy (MRS) by offering an improved signal‐to‐noise ratio and increased spectral resolution, thereby identifying more metabolites and extending the range of metabolic information. Spectroscopic data from clinical 1.5T MR scanners has been shown to discriminate between pediatric brain tumors by applying machine learning techniques to further aid diagnosis. The purpose of this multi‐center study was to investigate the discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…Two oversampling methods: data replication and SMOTE (Chawla et al, 2002;Zarinabad et al, 2018), were used to increase the ependymoma group size of training sets by 100%. The oversampled data was processed, with supervised learning, as above and results compared with no oversampling.…”
Section: Data Oversamplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Two oversampling methods: data replication and SMOTE (Chawla et al, 2002;Zarinabad et al, 2018), were used to increase the ependymoma group size of training sets by 100%. The oversampled data was processed, with supervised learning, as above and results compared with no oversampling.…”
Section: Data Oversamplingmentioning
confidence: 99%
“…The ability of a learning algorithm to discriminate between classes can be quantitatively determined using methods such as 'cross-validation' (Erickson et al, 2017). Previous results have shown the ability of supervised methods to separate between tumour subtypes and high/low grade tumours using magnetic resonance spectroscopy, with 1.5T and 3T results showing 79% and 86% balanced accuracy rate (BAR), respectively (Vicente et al, 2013;Zarinabad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent pattern recognition studies have been dealing with two aspects: first, diagnosis, performed mainly with SV, and second, delimitation of the abnormal area, performed with MRSI. One of the main reasons for this thematic restriction is that SV MRS can address a clinically relevant question, namely the added value of MRS to MRI for brain tumour type and grade assessment . Whatever the aspect addressed, all recent studies use a ‘targeted metabolomics’ approach, i.e.…”
Section: Mrs Cancer Patternmentioning
confidence: 99%
“…The fact that the curated INTERPRET dataset has been made accessible to research groups allows them to develop classifiers comparing single‐centre cohorts with that dataset, for example to differentiate abscesses from tumours at 3 T . Diagnosis of paediatric brain tumours has also been the subject of two recent works at 1.5 T on a large cohort of 90 patients and at 3 T in a multicentre study on 41 patients, to distinguish among the three main paediatric brain tumours (medulloblastoma versus pilocytic astrocytoma versus ependymoma). Despite this, single‐centre studies are still reported …”
Section: Mrs Cancer Patternmentioning
confidence: 99%